2008
DOI: 10.1007/s10803-008-0632-0
|View full text |Cite
|
Sign up to set email alerts
|

Anger, Stress Proliferation, and Depressed Mood Among Parents of Children with ASD: A Longitudinal Replication

Abstract: Stress proliferation (the tendency for stressors to create additional stressors) has been suggested as an important contributor to depression among caregivers. The present study utilized longitudinal data from 90 parents of children with ASD to replicate and extend a prior cross-sectional study on stress proliferation by Benson (J Autism Develop Disord 36:685-695, 2006). Consistent with Benson's earlier findings, regression analyses indicated that stress proliferation mediated the effect of child symptom sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
130
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(150 citation statements)
references
References 56 publications
(88 reference statements)
11
130
1
5
Order By: Relevance
“…32,33 When parents of children with disabilities experience poor health, they may be less able to care for their children, which sets up a vicious cycle of negative outcomes for all family members. 30,34 In fact, the physical health of parents is directly associated with the physical health of their children with cerebral palsy, and their mental health is significantly associated with the psychosocial function and total quality of life of their children. 35 Strategies that promote the health and well-being of parents might benefit the entire family through these complex, reciprocal interactions.…”
Section: Addressing the Needs Of Families Of Children With Disabilitimentioning
confidence: 99%
“…32,33 When parents of children with disabilities experience poor health, they may be less able to care for their children, which sets up a vicious cycle of negative outcomes for all family members. 30,34 In fact, the physical health of parents is directly associated with the physical health of their children with cerebral palsy, and their mental health is significantly associated with the psychosocial function and total quality of life of their children. 35 Strategies that promote the health and well-being of parents might benefit the entire family through these complex, reciprocal interactions.…”
Section: Addressing the Needs Of Families Of Children With Disabilitimentioning
confidence: 99%
“…No caso específico do autismo, alguns estudos mostraram que os pais de crianças com desordens do espectro do autismo apresentam um maior risco de depressão ou outros problemas de saúde mental do que os pais de crianças com outras problemáticas. Os progenitores parecem experimentar dimensões específicas de stress relacionadas com a variedade de sintomas e de problemas comportamentais da criança, podendo afetar negativamente o bem-estar parental e a saúde mental dos pais (Benson & Karlof, 2009).…”
Section: Discussionunclassified
“…Compared to mother caregivers of children with other disabilities, it has been reported that caregivers of children with ASD have higher levels of depression and anxiety but lower levels of psychological wellbeing (Benson & Karlof, 2009; Ekas, Whitman, & Shivers, 2009). Depression is a particularly prevalent psychological issue among mothers of children with ASD (Parkes et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%